2014
DOI: 10.3906/sag-1212-5
|View full text |Cite
|
Sign up to set email alerts
|

The increase of mean platelet volume in patients with Alzheimer disease

Abstract: Background/aim: Vascular risk factors play an important role in the progression of Alzheimer disease (AD). Mean platelet volume (MPV) is a determinant of platelet functionality and increased MPV is associated with an increased risk of vascular inflammation. Here we aimed to examine whether MPV could be used as a marker of vascular damage in AD and to discuss the relation between MPV and other vascular risk factors. Materials and methods:A total of 109 outpatients with AD and 81 healthy controls were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…Chen et al (2017), comparing the routine blood parameters of 92 patients with AD and 84 healthy controls, determined that MPV levels were significantly elevated in AD patients. Koc et al (2014) found that MPV levels were significantly elevated in AD patients and were associated with cognitive impairment severity. In our study, we also confirmed that the MPV was higher in MCI patients and had an optimal diagnostic value in distinguishing MCI patients from healthy controls.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Chen et al (2017), comparing the routine blood parameters of 92 patients with AD and 84 healthy controls, determined that MPV levels were significantly elevated in AD patients. Koc et al (2014) found that MPV levels were significantly elevated in AD patients and were associated with cognitive impairment severity. In our study, we also confirmed that the MPV was higher in MCI patients and had an optimal diagnostic value in distinguishing MCI patients from healthy controls.…”
Section: Discussionmentioning
confidence: 93%
“…MPV is a determining factor of platelet function, and an elevated MPV is correlated with vascular inflammation. Koc et al (2014) reported that MPV levels were higher in AD patients. Yesil et al (2012) also considered that an increased MPV was associated with vascular risk in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al reported significantly reduced MPV levels as cognitive levels declined and showed that MPV levels were significantly associated with MMSE (33) . Koç et al reported elevated MPV levels in patients with Alzheimer's disease but in that study when the patients were divided into 2 subgroups as having mild or moderate cognitive impairments according to MMSE scores, there was not any statistically significant difference between moderate and the mild groups regarding MPV values (15) . We also could not determine an association between serum MPV levels and cognitive functions.…”
Section: Discussionmentioning
confidence: 73%
“…Mean platelet volume (MPV) is a marker of activated platelets and has been associated with many inflammatory conditions (12)(13)(14). On the other hand, elevated MPV levels were also reported in patients with Alzheimer disease having cognitive impairments (15) .…”
Section: Introductionmentioning
confidence: 99%
“…Platelet activity can be assessed by simple platelet parameters such as platelet count (PLT), mean platelet volume (MPV) and platelet distribution width (PDW) routinely obtained during analysis of peripheral blood morphology [12][13][14]. Recent studies showed contradictory results concerning the relationship between MPV and cognitive performance [15][16][17][18][19]. Therefore, the aim of the study was to evaluate the relationship between basic platelet indices (PI) and the cognitive and functional performance of older patients admitted to the hospital ward.…”
Section: Introductionmentioning
confidence: 99%